Primary postpartum hemorrhage and associated factors among delivering women in Gedeo Zone, Southern Ethiopia - Zenebe, Getachew Assefa; Zenebe, Wagaye Alemu; Ewunie, Temesgen Muche; Dires, Selamawit (Frontiers in Medicine, 2023)
Introduction: Primary postpartum haemorrhage continues to be the leading cause of maternal mortality worldwide, particularly in low-resource countries like Ethiopia where there are inadequate health facilities and a shortage of qualified healthcare workers. Data on the prevalence of primary postpartum haemorrhage in the study population are scarce or nonexistent. Objective: The aim of this study was to assess the prevalence of primary postpartum haemorrhage and its associated factors among delivering women in Gedeo Zone, Southern Ethiopia, in 2021. Methods: A facility-based cross-sectional study was carried out from January 1 to March 30, 2021, in public health facilities in the Gedeo Zone. A randomly selected 577 participants were involved in the study. A pre-tested, structured, and interview-administered questionnaire was used to collect data. The collected data were entered into Epi Info version 3.5.1 software and analyzed using SPSS version 23. Descriptive data were presented using tables and graphs. A logistic regression model was fitted. A bivariable and multivariable logistic regression model was computed to identify the presence and strength of the association. To run multivariable logistic regression analyses, variables with P-values of less than 0.2 were used. The odds ratio, a 95% confidence interval (CI), and a P-value of less than 0.05 were used to identify variables that were associated with primary postpartum haemorrhage. Results: The magnitude of primary postpartum haemorrhage was 4.2% (95% CI: 2.4-6.0). Postpartum haemorrhage was significantly associated with current antepartum haemorrhage (AOR =11.67; 95%CI: 7.17-16.17), twin delivery (AOR = 6.59, 95%CI: 1.48-11.70), uterine atony (AOR = 8.45, 95%CI: 4.35-12.55), and prolonged labour (AOR = 5.6, 95%CI: 2.9-8.50). Conclusions: The prevalence of primary postpartum haemorrhages in the Gedeo zone, Southern Ethiopia was 4.2%. Current antepartum haemorrhage, twin delivery, uterine atony, and prolonged labour were predictors of primary postpartum haemorrhage. The findings support the need for care in the early postpartum period to enable clinicians to promptly detect any problems, prevent and initiate treatment for excessive blood loss early, and, considering the above factors, might decrease the magnitude of primary postpartum haemorrhage.